(3TQM JYdje GdeJYde WQjb GdJYde ddRQfhLjs - (3GdYKeGfj, GHf ESeGYjd, Rjf GdYQH, EHQGgje Hf ESeGYjd eMj GdOjf, cGf MjG (B996(3g`s ((3hdGjI SGeQs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CfYe YdjfG HCfhGY GdfYe hHYO adeG QCjJ GdcJGH GdeSei HJYdje GdeJYde eQZhHG ebHhdG CQOJ Cf CTQMg TQMG jHjf eYGbOgs
(3BNQgG (B:s
(3aj cJGH GdeSei HWH GdfHj Ydjg GdUdGI hGdSdGe, hcGf bGFdG bGd aCjf JLO gPG GdcJGH aCLGH jLOg ef jWdHg hgh cJGH eTghQ heYJHQ Hjf GdYdeGA adG HO ddWGdH ef Cf jLOg HGdBKGQ hGdCNHGQ GdePchQI ajgs
(3fSNI efbhdI ef fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf(B: 1 / 425s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs